PENGARUH LATIHAN HOLLAW SPRINT TERHADAP KECEPATAN PADA TIM SSB WONNER 2012 U-12 PEKANBARU - Al Muhyiddin Rauf; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is that the many athletes are less able to run fast when chasing a ball that is baited by their teammates. This type of research is a type of experimental research to see the effects of this form of exercise.the purpose of this research is to find out whether there is an effect of training Hollaw Sprint training on Speed on the Wonner 2012 U-12 Pekanbaru team. Population in this research is players SSB Wonner 2012 U-12 Pekanbaru which amounted to 15 people. The sampling technique is by using total sampling, in which the total population is sampled.The instrument in this research used a 30 meter run test. After that, the data were processed by statistics, to test the normality by lilifors test at a significant level of α (0.05).The hypothesis proposed is the effect of hollaw sprint training on the speed of Wonner 2012 U-12 Pekanbaru. Based on the results of the analysis, there is average pree test 5.54 and post test 5.12 there is an average increase of 0,42 with t test that t arithmetic = 21> from t table = 1.761. Means t arithmetic> t table.thus there is the effect of Hollaw Sprint training on the speed of the wonner 2012 U-12 Pekanbaru team.Key Words: Hollaw Sprint, Speed